2014
DOI: 10.1111/1471-0307.12117
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the composition and sensory properties of Croatian cheese in a lamb skin sack (Sir iz mišine) during ripening

Abstract: Croatian traditional cheese, which ripens in a lamb skin sack, was studied to determine compositional, biochemical and sensory changes over 60 days of ripening. The ripening time had a significant effect on the chemical, biochemical and sensory parameters, particularly on the medium-and long-chain free fatty acids (P < 0.05) and total FFAs (P < 0.001). At the end of ripening palmitic, oleic and stearic acids were the predominant FFAs. Cheese ripened for more than 45 days was less acceptable to consumers as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In addition, Tudor Kalit et al . ( 31 ) have shown that ripening for a longer time (60 days) results in less acceptable products due to intensive proteolysis and lipolysis.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Tudor Kalit et al . ( 31 ) have shown that ripening for a longer time (60 days) results in less acceptable products due to intensive proteolysis and lipolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Cheeses that ripen in a sack of animal skin are produced in Turkey, Lebanon, Croatia, Bosnia and Herzegovina, Montenegro (Yilmaz et al, 2005;Ceylan et al, 2007;Serhan et al, 2010;Kalit et al, 2014). These artisanal cheeses are relatively unexplored, except some Turkish and Lebanese cheese varieties (Yilmaz et al 2005;Ceylan et al 2007;Serhan et al 2010).…”
Section: Lipolysis In Non-european Raw Milk Cheesesmentioning
confidence: 99%
“…Although EVOO is mostly used fresh, it is not uncommon to use it to preserve various food groups e.g., vegetables, fish as well as dairy products [7]. Dairy products represent a significant part of the modern diet, and by choosing traditional cheeses, consumers not only show their concern for nature, the origin of raw materials and products, but also contribute to the preservation of traditions and support economic development [8,9], especially in areas with limited resources [10] such as islands [11].…”
Section: Introductionmentioning
confidence: 99%